(untitled) (World Bulletin of Social Sciences, 2023)
The article describes the goals and objectives of teaching Uzbek literature at the lessons of the Uzbek language in Russian-language schools, the problems of determining the content of education and ways to solve them. In particular, the selection of high-quality works of art from the new Uzbek literature, including an appeal to the works of famous writers, lexical and grammatical difficulties that cause respect and respect among representatives of Uzbek literature with their works, the desire to get acquainted with the work of Uzbek writers and poets.